Intraoral schwannomas: Presentation of a series of 12 cases - Sanchis, José-María (2013)
Introduction: Schwannomas are benign and not very frequent tumors of the peripheral nerves, derived from the nerve supporting Schwann cells. Study Design: Data were collected on the clinical manifestations (sex, age), location, size and symptonts of the lesions as well as the evolution time and the initial (presumption) diagnosis. Results: Twelve patients were documented, with a mean age of 29,5 ± 12,1 years (range 16-50) and a balanced gender distribution. The mean duration of the lesions was 42,17± 45,3 months. The lesion located in the floor of the mouth was the largest tumor, measuring about 4 cm in maximum diameter, while the average size of the 12 schwannomas was 2.04± 1.1 cm. Conclusion: We present 12 oral schwannomas diagnosed and treated over a period of 10 years. © Medicina Oral S. L. C.I.F. B 96689336 - eISSN: 1989-5488.